2019
DOI: 10.1182/bloodadvances.2018027003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the graft-versus-leukemia effect on survival in acute lymphoblastic leukemia

Abstract: Allogeneic hematopoietic cell transplant is a potential curative therapy for acute lymphoblastic leukemia (ALL). Delineating the graft-versus-leukemia (GVL) effect as a function of graft-versus-host disease (GVHD) offers the potential to improve survival. We examined 5215 transplant recipients with ALL reported to the Center for International Blood and Marrow Transplant Research registry. Overall survival (OS) was compared according to the presence and severity of GVHD and evaluated in 3 cohorts: 2593 adults i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
52
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 25 publications
9
52
2
Order By: Relevance
“…Despite the relative inefficacy of donor lymphocyte infusion (DLI) in the treatment of patients with post-transplant acute lymphoblastic leukaemia (ALL) relapses, several findings (such as a lower relapse incidence after allo-HSCT than after autologous stem cell transplantation, lower incidence of relapse in patients with GvHD, or a trend for higher risk of relapse in patients given grafts from syngeneic twins) have suggested potent GvL effects in ALL (Appelbaum, 1997;Stern et al, 2014). This was confirmed by a recent report from the Center for International Blood & Marrow Transplant Research (CIBMTR), which assessed the impact of occurrence of GvHD on allo-HSCT outcomes in a cohort of 5215 patients with ALL who had been given grafts from either a HLA-matched sibling donor, HLA-matched unrelated donor or cord blood transplantation (Yeshurun et al, 2019). In that report, the authors demonstrated that both acute and chronic GvHD protected from ALL relapse.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Despite the relative inefficacy of donor lymphocyte infusion (DLI) in the treatment of patients with post-transplant acute lymphoblastic leukaemia (ALL) relapses, several findings (such as a lower relapse incidence after allo-HSCT than after autologous stem cell transplantation, lower incidence of relapse in patients with GvHD, or a trend for higher risk of relapse in patients given grafts from syngeneic twins) have suggested potent GvL effects in ALL (Appelbaum, 1997;Stern et al, 2014). This was confirmed by a recent report from the Center for International Blood & Marrow Transplant Research (CIBMTR), which assessed the impact of occurrence of GvHD on allo-HSCT outcomes in a cohort of 5215 patients with ALL who had been given grafts from either a HLA-matched sibling donor, HLA-matched unrelated donor or cord blood transplantation (Yeshurun et al, 2019). In that report, the authors demonstrated that both acute and chronic GvHD protected from ALL relapse.…”
mentioning
confidence: 71%
“…However, only a mild form of acute GvHD (grades I-II) translated to improved overall survival (OS) in patients in first or second complete remission (CR) at transplantation. In contrast, chronic GvHD occurrence was associated with better OS in the subgroup of patients with advanced ALL (Yeshurun et al, 2019).…”
mentioning
confidence: 78%
“…Allo-HSCT with a strong graft vs. host leukemia (GvHL) effect is a very important form of immunotherapy in the treatment of Ph+ B-ALL patients [135]. However, high incidence of treatment-related mortality (up to 40%) and high rates of acute and chronic graft vs. host disease are limiting the widespread use of allo-HSCT [136].…”
Section: Regimenmentioning
confidence: 99%
“…Interestingly, several studies have demonstrated that VZV infection may trigger chronic GVHD following allogeneic HSCT [19][20][21]. GVHD is associated with GVC effects and provided GVHD is of low-grade, it can be associated with improvement in OS in patients with acute leukemia or lymphoma [22][23][24].…”
Section: Graft Versus Host Disease and Its Association With Vzvmentioning
confidence: 99%